Sex- and tissue-specific functions of Drosophila doublesex transcription factor target genes. - Clough, E.; Jimenez, E.; Kim, Y.A.; Whitworth, C.; Neville, M.C.; Hempel, L.U.; Pavlou, H.J.; Chen, Z.X.; Sturgill, D.; Dale, R.K.; Smith, H.E.; Przytycka, T.M.; et al. (Developmental Cell, 2014)
Primary sex-determination "switches" evolve rapidly, but Doublesex (DSX)-related transcription factors (DMRTs) act downstream of these switches to control sexual development in most animal species. Drosophila dsx encodes female- and male-specific isoforms (DSX(F) and DSX(M)), but little is known about how dsx controls sexual development, whether DSX(F) and DSX(M) bind different targets, or how DSX proteins direct different outcomes in diverse tissues. We undertook genome-wide analyses to identify DSX targets using in vivo occupancy, binding site prediction, and evolutionary conservation. We find that DSX(F) and DSX(M) bind thousands of the same targets in multiple tissues in both sexes, yet these targets have sex- and tissue-specific functions. Interestingly, DSX targets show considerable overlap with targets identified for mouse DMRT1. DSX targets include transcription factors and signaling pathway components providing for direct and indirect regulation of sex-biased expression.